PERKEMBANGAN FATWA DI INDONESIA - Fatkul Mujib (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
This paper provides an overview of the process memutusakan a fatwa. Historical development of Islamic law in Indonesia that are specifically related to the issue of fatwa has brought a significant influence in the social life of the Muslim community. Community organizations in Indonesia has its own method of making a fatwa, like Muhammadiyah, Nahdlatul Ulama, Persis and MUI and others. With a variety of different methods, the decision fatwa produced sometimes also different. In Indonesia, the decision related organizations with specific statmen a problem can not be underestimated. So each has influence and obedience are together. Though there MUI, then each organization still using the referral of the organizations that they profess. So it is not surprising that sometimes there is a fatwa different from each institution to give fatwa. But although there is a difference, the associated social harmony still be maintained. Here's the interesting part of Indonesia.